2008
DOI: 10.1185/03007990802215844
|View full text |Cite
|
Sign up to set email alerts
|

Study of anemia in long-term care (SALT): prevalence of anemia and its relationship with the risk of falls in nursing home residents

Abstract: Anemia in nursing home residents appears to be under-recognized. For residents over 70 years, the prevalence of anemia in both male and female residents was approximately four times the rate reported in a study of older community dwellers (Salive et al., 1992). Both anemia and the use of psychoactive medications are potentially modifiable factors strongly associated with falling. Since falls and related fractures are events associated with high morbidity and mortality, each of these factors deserves special co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…Similar prevalence has been found in the Longitudinal Ageing Study Amsterdam [11] and in the InChianti Study [12]. Anemia prevalence increases rapidly after the age of 50, approaching a rate of over 20% in elderly aged 85 years or older [10], and has been found to be up to 65% among nursing home residents [8]. In one third of the elderly in the NHANES III, anemia could not be explained by malnutrition or underlying disease [10].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar prevalence has been found in the Longitudinal Ageing Study Amsterdam [11] and in the InChianti Study [12]. Anemia prevalence increases rapidly after the age of 50, approaching a rate of over 20% in elderly aged 85 years or older [10], and has been found to be up to 65% among nursing home residents [8]. In one third of the elderly in the NHANES III, anemia could not be explained by malnutrition or underlying disease [10].…”
Section: Introductionsupporting
confidence: 69%
“…Falls are also associated with high societal costs [6]. Previous studies have found various risk factors for falls in elderly people, including use of medications like sedatives [2, 7, 8], analgesics and antiepileptics [1], urinary incontinence [1], abnormalities in balance and gait, as well as other disabilities [1, 2, 8]. Due to the serious consequences, the identification of modifiable risk factors for falls of elderly people is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in non-dialysis patients demonstrated that anemia correlates with falls and with mobility dysfunctions in patients with chronic kidney disease. Pandya et al [30] showed that anemia in nursing home residents was associated with more than twice the risk of falling. These results were confirmed by Duh et al [31], who showed that anemia was significantly and independently associated with a risk increase for injurious falls.…”
Section: Discussionmentioning
confidence: 99%
“…Among institutionalized elderly patients, anemia was associated with an overall 1.9-to 2.2-fold increased risk of falls, 25,26 a level of risk similar to the use of psychoactive medications or age 85 years and over. 26 In models examining the effect of hemoglobin level on the incidence of falls after adjusting for age, gender, and race, the risk of falls decreased by 22% for every 1.0 g/dL increase in hemoglobin in the elderly individuals. 25 Among residents in long-term care facilities in Israel, the presence of anemia was also an independent risk factor for infections with drug-resistant Escherichia coli and Klebsiella pneumoniae , an association which matched that observed for previous antibiotic use.…”
Section: Discussionmentioning
confidence: 99%